Shielding type ultra-high-temperature-resistant compensation cable

By employing a shielded, high-temperature resistant structure composed of alloy wires, insulation layers, wrapping tape, and glass fiber braided layers in the compensating cable, the problem of insulation material aging in existing cables under high-temperature environments has been solved, achieving improved cable shielding and mechanical performance under high-temperature conditions.

CN121393997APending Publication Date: 2026-01-23JIANGSU JINLING SPECIAL CABLE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511498372.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-20
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

Existing compensating cables are prone to aging of insulation and sheath materials in high-temperature environments, failing to meet the requirements for use in high-temperature applications of 500℃~800℃, thus affecting the cable's service life and safety.

Method used

It uses alloy wire as the conductor, with an outer insulation layer and wrapping tape, filled with insulating material and copper wire shielding layer. The outer sheath is a glass fiber braided layer and a mica tape wrapping layer, combined with special ceramicized insulating material to form a high-temperature resistant shielding structure. It uses copper wire or tin-plated copper wire to shield high and low frequency electromagnetic interference, and enhances mechanical strength and fire resistance.

Benefits of technology

It achieves insulation and shielding performance of cables in high-temperature environments above 800℃, shields high and low frequency electromagnetic interference, has high mechanical strength, good bending performance, provides excellent fire resistance and mechanical impact resistance, and improves the service life and safety of cables.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121393997A_ABST
    Figure CN121393997A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of cable manufacturing, and particularly discloses a shielding type super-high-temperature-resistant compensation cable which comprises alloy wires, every two alloy wires form a group, the four alloy wires are distributed in a rectangular array mode, the outer wall of an insulating layer is fixedly connected with a shielding layer, the outer wall of the shielding layer is fixedly connected with a filling layer, and the outer wall of the filling layer is fixedly connected with an insulating layer. The outer wall of the filling layer is fixedly connected with outer sheaths, a first layer of wrapping tape is fixedly connected between the insulating layer and the shielding layer, the number of the outer sheaths is two, and a fourth layer of wrapping tape is arranged between the two outer sheaths; the preparation method comprises the following steps: S1, preparing the insulated wire core; s2, cable core cabling and filling; s3, preparing a shielding layer; and S4, preparing an outer sheath. Through the copper wire or tinned copper wire shielding layer and the galvanized steel wire armor layer, high and low frequency electromagnetic wave interference is effectively shielded, the mechanical strength is high, the bending performance is good, and the glass fiber filament braid layer and the mica tape wrapping layer provide excellent fire resistance and mechanical shock resistance.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application relates to the technical field of cable manufacturing, in particular to a shielded special high-temperature-resistant compensation cable. BACKGROUND

[0002] In the development process of modern industry and high-tech fields, many application scenarios have extremely strict requirements on the performance of cables. In particular, in some high-temperature environments, such as the engine surrounding environment in the aerospace field, the temperature in the local area often exceeds 600 DEG C; the temperature near the high-temperature steam pipeline in the nuclear island is also high; the smelting, glass manufacturing and other industries are also in a high-temperature state for a long time. In these scenarios, the cable not only needs to undertake the task of power transmission, but also shoulders the key responsibility of signal transmission to ensure the precise control and stable operation of the equipment.

[0003] In high-temperature fields such as steelmaking, petroleum, chemical industry, smelting, etc., the ambient temperature is usually as high as 500 DEG C to 800 DEG C, and the existing compensation cable national standard GB / T4989-1994 stipulates that fluoropolymer insulation glass fiber braid sheath is used in high-temperature resistant occasions, and its long-term temperature resistance level is only 200 DEG C. When the temperature reaches 350 DEG C, it will gradually melt, which cannot meet the use requirements of the above high-temperature occasions. If it is used forcibly, the insulation and sheath material will age quickly, which seriously affects the service life and safety of the cable. SUMMARY

[0004] In order to solve the problem that the fluoropolymer insulation glass fiber braid sheath has a long-term temperature resistance level of only 200 DEG C and gradually melts when the temperature reaches 350 DEG C, which cannot meet the use requirements of high-temperature occasions, the application provides a shielded special high-temperature-resistant compensation cable.

[0005] In the first aspect, the application provides a shielded special high-temperature-resistant compensation cable, which adopts the following technical scheme: a shielded special high-temperature-resistant compensation cable, comprising an alloy wire, the alloy wire is two groups, the alloy wire is arranged in a rectangular array distribution four groups, the outer wall of the plurality of alloy wires is fixedly connected with an insulation layer, the outer wall of the insulation layer is fixedly connected with a shielding layer, the outer wall of the shielding layer is fixedly connected with a filling layer, the outer wall of the filling layer is fixedly connected with an outer sheath, the insulation layer and the shielding layer are fixedly connected with a first layer of wrapping tape, the shielding layer and the filling layer are provided with a second layer of wrapping tape, the filling layer and the outer sheath are provided with a third layer of wrapping tape, and the outer sheath is provided with two layers and is provided with a fourth layer of wrapping tape in the middle.

[0006] By adopting the technical scheme, since the alloy wire is adopted, the alloy wire is surrounded by an insulating layer, and the insulating layer is further provided with a wrapping tape, in the whole cable structure, four alloy wire combination materials are provided, the gaps between the four alloy wire combination materials are filled with insulating materials and copper wire or tinned copper wire shielding layer shielding materials, and finally the whole outer sheath is used to wrap up the structure, the outer sheath is made of a glass fiber braid layer and a mica tape wrapping layer, the shielding performance is excellent, the copper wire or tinned copper wire shielding layer and the galvanized steel wire armor layer effectively shield high and low frequency electromagnetic wave interference, and the mechanical strength is high and the bending performance is good, and the glass fiber braid layer and the mica tape wrapping layer provide excellent fire resistance and mechanical impact resistance.

[0007] In a second aspect, the application provides a preparation method of the shielding type special high-temperature-resistant compensation cable, which adopts the following technical scheme: The preparation method of the shielding type special high-temperature-resistant compensation cable comprises the following steps: S1, a composite ceramicized insulating material is coated on the alloy wire conductor, cross-linking vulcanization is performed, an insulating layer is formed, a first layer of wrapping tape is wrapped outside the insulating layer, and an insulating wire core is obtained; S2, a plurality of insulating wire cores are stranded into a cable, and during the stranding process, light thermal insulation composite filling material is filled into the gaps between the insulating wire cores and is solidified to form a filling layer, a cable core is obtained; S3, a second layer of wrapping tape, a metal shielding layer formed by braiding, and a third layer of wrapping tape are wrapped outside the cable core in sequence; S4, a reinforcing fiber skeleton is braided outside the third layer of wrapping tape, and the reinforcing fiber skeleton is subjected to impregnation coating and programmed heating and solidification treatment to form an outer sheath.

[0008] Preferably, in the step S1, the composite ceramicized insulating material comprises, in parts by mass, 100 parts of methyl vinyl silicone rubber, 40-60 parts of ceramicized filler, 15-25 parts of fumed white carbon black, 5-15 parts of zinc borate, and 5-10 parts of flaky hexagonal boron nitride.

[0009] Preferably, in the step S2, a pretreatment step of performing surface chemical modification on the silica aerogel and hollow glass microsphere as light thermal insulation fillers by using a silane coupling agent is further included before filling.

[0010] Preferably, in the step S2, the light thermal insulation composite filling material is made of raw materials including a two-component addition type liquid silicone rubber, the silica aerogel and the hollow glass microsphere subjected to surface chemical modification, and an aluminum hydroxide flame retardant.

[0011] Preferably, in the step S4, the reinforcing fiber skeleton is a continuous basalt fiber braid layer.

[0012] Preferably, in the step S4, the impregnated coating material is an organic and inorganic nanocomposite coating liquid, and the composite coating liquid is prepared from raw materials including a silicone-modified polyimide emulsion, a silica sol of an inorganic binder, and a nano-silicon carbide wear-resistant filler.

[0013] Preferably, in the step S4, the programmed heating and curing process includes the following steps: The impregnated cable semi-finished product is sent into a heating temperature zone, and the heating temperature zone includes three regions. The temperature of the first region is 80-100°C, the temperature of the second region is 150-200°C, and the temperature of the third region is 250-300°C, so that the outer sheath is built into an organic and inorganic interpenetrating network structure.

[0014] Preferably, in the step S2, the insulated core is stranded at a pitch of 80-120 mm, and the filled cable core is cured online by an infrared heating channel at 130-150°C.

[0015] Preferably, in the step S3, the metal shielding layer is woven by a tin-plated copper wire with a diameter of 0.10-0.15 mm, and the coverage is ≥85%; After the preparation, the following steps are performed: A fourth layer of wrapping tape is wrapped around the outer sheath, and the step S4 is repeated completely to prepare a second layer of outer sheath.

[0016] In summary, the present application has the following beneficial effects: 1. Due to the copper wire or tin-plated copper wire shielding layer and the galvanized steel wire armor layer, the present application effectively shields high and low frequency electromagnetic wave interference, and has high mechanical strength and good bending performance. The glass fiber woven layer and the mica tape wrapping layer provide excellent fire resistance and mechanical impact resistance.

[0017] 2. In the present application, by adding flaky hexagonal boron nitride in the composite ceramic insulation material and inducing radial orientation, efficient radial heat conduction in normal state and in-situ formation of dense ceramic insulator in fire are realized, so that the effects of excellent working heat dissipation performance and circuit integrity at extremely high temperature are considered.

[0018] 3. In the method of the present application, the surface-modified silica aerogel and hollow glass microspheres are used as composite fillers, so as to build a lightweight thermal insulation layer with strong interfacial adhesion and low thermal conductivity inside the cable core, thereby significantly improving the overall thermal insulation performance of the cable and reducing the weight of the cable. BRIEF DESCRIPTION OF DRAWINGS

[0019] Figure 1 is a structural schematic diagram of a shielding type high-temperature-resistant compensation cable provided by the present application; Figure 2 is a method flow chart of a preparation method of a shielding type high-temperature-resistant compensation cable provided by the present application.

[0020] 1, alloy wire; 2, insulation layer; 3, shielding layer; 4, filling layer; 5, outer sheath; 6, wrapping tape. DETAILED DESCRIPTION

[0021] The present application will be further described in detail below in combination with the drawings and examples.

[0022] The general status of the related art in the art is that in high-temperature occasions such as steelmaking, petroleum, chemical industry, smelting, etc., the ambient temperature is usually as high as 500-800℃, and the existing compensation cable national standard GB / T4989-1994 stipulates that fluoropolymer insulation glass fiber braid sheath is used in high-temperature occasions, and its long-term temperature resistance grade is only 200℃, which will gradually melt when the temperature reaches 350℃, and it cannot meet the use requirements in the above high-temperature occasions. If it is forcibly used, the insulation and sheath material will quickly age, seriously affecting the service life and safety of the cable.

[0023] The present application solves the above problems by the following means: the alloy wire is a compensation conductor alloy wire, a layer of insulation layer is wrapped around the alloy wire, a wrapping tape is further provided outside the insulation layer, a copper wire or tinned copper wire shielding layer and a galvanized steel wire armor layer, which effectively shields high and low frequency electromagnetic wave interference, and has high mechanical strength and good bending performance. The glass fiber braid layer and the mica tape wrapping layer provide excellent fire resistance and mechanical impact resistance, and then a special ceramic insulation material is used. When it encounters ultra-high temperature, it will not melt like traditional materials, but will sinter to form a hard ceramic shell, maintain the insulation function and structure, and increase the temperature resistance limit from 200℃ to above 800℃.

[0024] The following materials are conventional materials of the prior art unless otherwise specified.

[0025] The methyl vinyl silicone rubber (VMQ) is commercially available industrial grade with the product number 67762-949-1 from Chongqing Ruiya Biological Technology Co., Ltd.

[0026] The ceramic filler: calcined kaolin 400 mesh and acicular wollastonite powder with an aspect ratio of 15:1 are premixed in a mass ratio of 3:1, the calcined kaolin is product number A00155 from Wuhan Jiyue Shenghua Chemical Co., Ltd., and the acicular wollastonite powder is CAS: 1344-95-2 from Shanghai Tianhan Mineral Powder Technology Co., Ltd.

[0027] The fumed white carbon black is product number T25658 from Shanghai Yuanye Biological Technology Co., Ltd.

[0028] The zinc borate is product number GA3235 from Hubei Guangao Biological Technology Co., Ltd.

[0029] Flaky hexagonal boron nitride h-BN: average flake diameter 10 pm, thermal conductivity > 200 W / (m K), commercially available.

[0030] Two-component addition type liquid silicone rubber (LSR): A / B components, viscosity 5000 mPas, Dongguan Hongfeng Haogong Technology Co., Ltd., item number HF-7509.

[0031] Silica aerogel particles: particle size 40 pm, thermal conductivity < 0.02 W / (m K), Xi'an Qiyue Biological Technology Co., Ltd., item number 16352.

[0032] Hollow glass microbeads: particle size 50 pm, compressive strength > 20 MPa, commercially available.

[0033] Aluminum hydroxide (ATH): average particle size 2.5 pm, commercially available.

[0034] Soft annealed tinned copper wire: single wire diameter, commercially available.

[0035] PTFE film tape: thickness 0.1 mm, commercially available.

[0036] Continuous basalt fiber yarn: linear density 400 tex, commercially available.

[0037] Silica sol: SiO2content 30%, basic, particle size 20 nm, commercially available.

[0038] Nano silicon carbide (alpha-SiC) powder: average particle size 60 nm, commercially available.

[0039] Please refer to Figure 1 A shielding type high-temperature-resistant compensation cable includes alloy wires 1, two of which form a group, the alloy wires 1 are arranged in a rectangular array to form four groups, the outer walls of the plurality of alloy wires 1 are fixedly connected with insulating layers 2, the outer walls of the insulating layers 2 are fixedly connected with shielding layers 3, the outer walls of the shielding layers 3 are fixedly connected with filling layers 4, the outer walls of the filling layers 4 are fixedly connected with outer sheaths 5, the insulating layers 2 and the shielding layers 3 are fixedly connected with first layer wrapping tapes 6, the shielding layers 3 and the filling layers 4 are provided with second layer wrapping tapes 6, the filling layers 4 and the outer sheaths 5 are provided with third layer wrapping tapes 6, and the outer sheaths 5 are provided with two layers and are provided with fourth layer wrapping tapes 6 in the middle.

[0040] The structure of the cable is the most inside alloy wire, the alloy wire is the compensation conductor alloy wire, the alloy wire is surrounded by an insulating layer, and the insulating layer is further provided with a wrapping tape. In the whole cable structure, four alloy wire combination materials are provided. The gaps between the four alloy wire combination materials are filled with insulating materials and copper wire or tin-plated copper wire shielding layer shielding materials. Finally, the whole outer sheath is used to wrap up the structure, and the outer sheath is made of glass fiber braid layer and mica tape wrapping layer, which solves the main defects of the prior art, including limited shielding performance, easy to be interfered by high and low frequency electromagnetic waves, can be used as compensation conductor, compensation cable and thermocouple matching, used for temperature measurement and control system of power, metallurgy, petroleum, chemical industry, light textile and other factories and scientific research departments, through the copper wire or tin-plated copper wire shielding layer and galvanized steel wire armor layer, the high and low frequency electromagnetic wave interference is effectively shielded, and the mechanical strength is high, the bending performance is good, and the glass fiber braid layer and mica tape wrapping layer provide excellent fire resistance and mechanical impact resistance.

[0041] Preparation Example 1: The lightweight thermal insulation composite filler is made of silica aerogel and hollow glass microspheres, liquid silicone rubber and aluminum hydroxide modified by a silane coupling agent. The silane coupling agent is selected from gamma-methacryloxypropyltrimethoxysilane (KH-570), gamma-aminopropyltriethoxysilane (KH-550) or gamma-glycidyl ether propyltrimethoxysilane (KH-560).

[0042] Specifically, the preparation method of the lightweight thermal insulation composite filler comprises the following steps: Step 1, preparation of coupling agent hydrolysis solution: In a 500 mL beaker, 10 g of KH-570, 100 g of anhydrous ethanol and 20 g of deionized water were added, and stirred uniformly. Then, 0.1 mol / L hydrochloric acid was used to adjust the pH to 3.5-4.0. The weak acid condition accelerates the hydrolysis, and avoids excessive condensation of the coupling agent.

[0043] Stir for 30 minutes at room temperature until the solution is clear and transparent to generate a hydrolysis product containing silicon hydroxyl groups: KH-570-Si-OH.

[0044] Step 2, mixing and modification of fillers: In a 2000 mL high-speed mixer, 200 g of silica aerogel and 150 g of hollow glass microspheres were added, and stirred at a low speed of 300 r / min for 10 minutes to uniformly disperse the two fillers.

[0045] The prepared KH-570 hydrolysis solution was slowly sprayed into the mixed fillers, and stirred while spraying. The spraying time was controlled within 15 minutes to uniformly coat the surface of each particle with the hydrolysis solution.

[0046] Step 3, drying and activation: The modified mixed filler is transferred to a vacuum drying oven, dried at 60°C and a vacuum degree of -0.08 MPa for 2 hours, low-temperature drying avoids the collapse of aerogel structure, and removes ethanol and moisture to obtain a surface-modified aerogel-hollow microsphere composite filler.

[0047] Step 3, compounding and curing of the composite filler: In a 10L planetary mixer, 250g of the silicone rubber A component is added, stirring is started at a speed of 500r / min, and 150g of the modified composite filler is added in three portions with an interval of 10 minutes, so that the filler is gradually wrapped by the silicone rubber to avoid scattering; 130g of aluminum hydroxide flame retardant is added, the stirring speed is increased to 800r / min, and mixing is performed for 30 minutes, at which time the system is thick paste without obvious particle agglomeration.

[0048] The stirring speed is reduced to 300r / min, 250g of the silicone rubber B component is added, and stirring is performed for 20 minutes to fully mix the A and B components, which can be observed by sampling: the paste is uniform in color without white stripes.

[0049] The mixer is turned off, the vacuum system is turned on, the vacuum degree is -0.09 MPa, and the air bubbles introduced during mixing are removed for 15 minutes.

[0050] The defoamed paste material is poured into an open mold with a thickness of 5cm, and placed in a 130°C infrared heating oven for 60 minutes to obtain a block-shaped lightweight filler.

[0051] The cooled block-shaped material is crushed into particles with a particle size of 2-5mm using a crusher, and the final lightweight thermal insulation composite filler is obtained.

[0052] Preparation Example 2: The composite coating liquid is prepared from raw materials including silicone-modified polyimide emulsion, inorganic binder silica sol, and nano-silicon carbide wear-resistant filler.

[0053] Specifically, the preparation steps of the composite coating liquid are as follows: Step 1: Surface pretreatment of nano-silicon carbide Weighing and dispersing: 100g of nano-silicon carbide powder is taken into a 500mL beaker, 300mL of anhydrous ethanol is added, and stirring is performed to wet the powder.

[0054] Silane coupling agent modification: 3g of silane coupling agent KH-550 is added, the amount is 3% of the mass of SiC, 0.1mol / L hydrochloric acid is used to adjust the pH to 4.0-4.5, and the mixture is placed in an ultrasonic cleaner with a power of 300W for ultrasonic dispersion for 30 minutes to react the coupling agent with the SiC surface hydroxyl groups.

[0055] Drying and activation: The dispersion was dried in a vacuum oven at 80°C, vacuum degree -0.08 MPa, to obtain surface-modified nano-SiC powder, which was ground through a 200-mesh sieve for use. The SiC after treatment was more easily dispersed in the organic phase.

[0056] Step 2: Mixing the organic phase (Si-PI emulsion) with the inorganic phase (silica sol) Preparation of base solution: In a 1000-mL four-necked flask, 500 g of organosilicon-modified polyimide emulsion (40% solid content) was added, stirring was started at a speed of 200 r / min, and 250 g of silica sol (30% solid content) was slowly added while stirring to avoid local agglomeration. After the addition was completed, stirring was continued for 30 minutes to obtain an organic-inorganic mixed base solution.

[0057] pH adjustment: The pH of the mixed base solution was adjusted to 7.0-7.5 using 0.5 mol / L ammonia water. Neutral conditions can improve the stability of the silica sol and prevent premature gelation.

[0058] Step 3: Adding nano-silicon carbide and dispersing The pre-treated nano-SiC powder from Step 1, 150 g, was added in three portions to the mixed base solution at a ratio of 15 parts. After each addition, the solution was stirred for 10 minutes at an increased speed of 400 r / min to ensure that the powder was wetted.

[0059] High-speed dispersion: 0.75 g of dispersant BYK-110 was added, and the stirring speed was increased to 800 r / min. The dispersion was carried out for 60 minutes, during which the particle size distribution of SiC was monitored using a laser particle size analyzer. The D50 value was required to be ≤100 nm, and there should be no significant agglomeration.

[0060] Ultrasonic-assisted dispersion: The mixed solution was transferred to an ultrasonic reactor, and ultrasonic treatment was carried out at a power of 500 W for 20 minutes to further break up the small agglomerates.

[0061] Step 4: Viscosity adjustment and filtration Viscosity test: The current viscosity was measured using a rotary viscometer at 25°C and a stirring speed of 60 r / min. If the viscosity was higher than 800 mPa·s, DMAc solvent was slowly added in 50-mL increments, and the solution was stirred for 10 minutes before retesting. The viscosity was adjusted to be stable within the range of 500-800 mPa·s. This range was suitable for the impregnation coating of basalt fiber skeletons, ensuring uniform coating without dripping.

[0062] Filtration to remove impurities: The coating solution was filtered using a 100-mesh nylon filter cloth to remove possible large particle impurities, and the final composite coating solution was obtained. The appearance should be a uniform gray fluid with no obvious sedimentation.

[0063] The organosilicon-modified polyimide emulsion was prepared using a two-step modification method. The specific steps included: Step 1: Hydrolysis of silane coupling agent Preparation of hydrolysis solution: In a 500 mL three-necked flask, the raw materials were added in a volume ratio of silane coupling agent KH-570: deionized water: anhydrous ethanol = 1:2:3, 20 mL of KH-570, 40 mL of deionized water, and 60 mL of anhydrous ethanol.

[0064] Adjusting pH: The pH of the mixture was adjusted to 3.5-4.0 with 0.1 mol / L hydrochloric acid, and the weakly acidic conditions accelerated the hydrolysis to avoid excessive condensation.

[0065] Hydrolysis reaction: Stirring in a 30°C water bath at 300 r / min for 30-40 minutes until the solution is clear and transparent without stratification or precipitation, obtaining the hydrolyzed silane solution containing silicon hydroxyl groups (-Si-OH).

[0066] Step 2: Graft modification of polyimide emulsion Emulsion pretreatment: Take 1000g of PEI-P-20G emulsion, solid content is 35%, containing 350g of polyimide, add to a 500mL four-necked flask, heat to 50°C, stirring speed 200r / min, preheat for 10 minutes.

[0067] Dropwise addition of silane hydrolysis solution: Slowly drop about 120mL of silane hydrolysis solution prepared in Step 1 into the polyimide emulsion through a constant pressure dropping funnel, the dropwise addition speed is controlled at 1-2 drops per second, keep stirring at 50°C throughout the process, continue to react for 30 minutes after the dropwise addition is completed.

[0068] Catalytic grafting: Add 0.5g of catalyst, the catalyst is dibutyltin dilaurate (DBTDL), the catalyst dosage is 0.14% of the mass of polyimide, heat to 60°C, increase the stirring speed to 400r / min, react for 2 hours, monitor by infrared spectrum: 1080cm -1 Si-O-Si characteristic peak appears, indicating successful grafting.

[0069] Step 3: Performance adjustment and post-treatment Adjusting solid content: After the reaction is completed, measure the current emulsion solid content, about 32-36%, add appropriate amount of N,N-dimethylacetamide (DMAc) for dilution or distill under reduced pressure at 40°C, vacuum degree -0.08MPa, accurately adjust the solid content to 40%.

[0070] Filtering and removing impurities: Filter the emulsion with 100 mesh nylon filter cloth to remove a small amount of gel particles that may be generated, obtaining clear Si-PI modified emulsion.

[0071] Aging stability: After sealing, place the emulsion in a 25°C constant temperature oven for 24 hours, let the remaining active groups fully react to improve stability.

[0072] Grafting rate detection requires grafting rate ≥ 5% to make silicone group enough to be introduced. High temperature resistance verification: coating the emulsion on aluminum foil with a thickness of 0.1mm, following the curing temperature ladder in S4 step in Example 1 below, then burning in muffle furnace at 800℃ for 30 minutes, observing whether the coating remains intact, no cracking, falling off, and the residual compressive strength ≥ 8MPa.

[0073] Silica sol compatibility test: mix the modified emulsion with silica sol 30% solid content at a mass ratio of 7:3, observe whether it is stratified after stirring for 30 minutes, and it is qualified within 24 hours without stratification, forming an organic-inorganic interpenetrating network.

[0074] Wear resistance test: after curing on basalt fiber cloth, perform Taber wear test, 1kg load, CS-17 grinding wheel, wear ≤30mg / 1000r.

[0075] Example 1: Please refer to Figure 2 A preparation method of a shielding type high temperature resistant compensation cable, the specific steps are as follows: S1, insulation core preparation: 100 parts of methyl vinyl silicone rubber, 40 parts of ceramic filler, 15 parts of fumed white carbon black, 5 parts of zinc borate and 5 parts of flaky hexagonal boron nitride are uniformly mixed in an internal mixer to form a composite ceramic insulation material. The insulation material is coated on the alloy wire 1 conductor and vulcanized to form an insulation layer 2, and then a first layer of wrapping tape 6 is wrapped to obtain an insulation core.

[0076] S2, cable core cabling and filling: a plurality of insulation cores are twisted into a cable with a pitch of 80mm, and a light weight heat insulation composite filler is filled into the gap between the insulation cores. Through an infrared heating channel at 130℃, the filler is cured in line to form a filling layer 4, and a cable core is obtained.

[0077] S3, shielding layer preparation: a second layer of wrapping tape 6 is wrapped outside the cable core, and then a metal shielding layer 3 with a coverage rate of ≥85% is formed by weaving a tin-plated copper wire with a diameter of 0.10mm, and a third layer of wrapping tape 6 is wrapped.

[0078] S4, outer sheath preparation: a continuous basalt fiber reinforced skeleton is woven outside the third layer of wrapping tape 6, and after impregnating the composite coating liquid, it is sent into a three-zone drying channel for programmed heating and curing. The temperature of the first zone is 80℃, the temperature of the second zone is 150℃, and the temperature of the third zone is 250℃, forming an outer sheath 5.

[0079] Example 2: The preparation method of this example is basically the same as that of Example 1, the main difference is: In S1 step, the composition of the composite ceramic insulation material is: 100 parts of methyl vinyl silicone rubber, 50 parts of ceramic filler, 20 parts of fumed white carbon, 10 parts of zinc borate, 7.5 parts of flaky hexagonal boron nitride.

[0080] In the S2 step, the insulated core is stranded at a pitch of 100 mm, and the infrared heating channel temperature is 140°C.

[0081] In the S3 step, the metal shielding layer is woven by tin-plated copper wire with a diameter of 0.125 mm.

[0082] In the S4 step, the programmed heating and curing temperature is 90°C for the first zone, 175°C for the second zone, and 275°C for the third zone.

[0083] Example 3: The preparation method of this example is basically the same as that of Example 1, the main difference is: In the S1 step, the composite ceramic insulation material components are: 100 parts of methyl vinyl silicone rubber, 60 parts of ceramic filler, 25 parts of fumed white carbon, 15 parts of zinc borate, 10 parts of flaky hexagonal boron nitride.

[0084] In the S2 step, the insulated core is stranded at a pitch of 120 mm, and the infrared heating channel temperature is 150°C.

[0085] In the S3 step, the metal shielding layer is woven by tin-plated copper wire with a diameter of 0.15 mm.

[0086] In the S4 step, the programmed heating and curing temperature is 100°C for the first zone, 200°C for the second zone, and 300°C for the third zone.

[0087] After S4: A fourth layer of wrapping tape 6 is wrapped around the outer sheath 5 formed by the first layer, and step S4 is repeated completely to prepare a second layer of outer sheath, further enhancing its environmental performance.

[0088] Comparative Example 1: The insulation layer uses ordinary silicone rubber without ceramic filler and flaky hexagonal boron nitride, the gap between the insulated cores is not filled with any material during cabling, the shielding layer is directly woven with ordinary glass fiber, and a layer of conventional silicone resin is coated and dried as a sheath.

[0089] Comparative Example 2: The preparation method is basically the same as that of Example 2, the difference is that in step S4, the material for immersion coating is silicone-modified polyimide emulsion without silica sol, and after curing, only a single organic polymer network is formed.

[0090] Comparative Example 3: The preparation method is basically the same as that of Example 2, except that in step S1, no flaky hexagonal boron nitride is added in the insulating material; and in step S2, the filling material uses equal mass of common precipitated silica instead of the surface-modified silica aerogel and hollow glass microbeads.

[0091] Comparative Example 4: The preparation method is basically the same as that of Example 2, except that in step S2, the silica aerogel and hollow glass microbeads used are not subjected to surface chemical modification treatment with silane coupling agent, and are directly used to prepare the filling material.

[0092] Comparative Example 5: The preparation method is basically the same as that of Example 2, except that in step S4, the reinforcing fiber skeleton uses common high-silica glass fiber instead of continuous basalt fiber.

[0093] Comparative Example 6: The preparation method is basically the same as that of Example 2, except that in step S4, the programmed heating and curing treatment is replaced by single-stage high-temperature baking, directly baking at 280°C for 30 minutes without stepwise temperature rising.

[0094] Comparative Example 7: The preparation method is basically the same as that of Example 2, except that in step S4, the impregnated coating material uses common epoxy resin varnish without silicone-modified polyimide and nano silicon carbide instead of the organic and inorganic nano composite coating liquid.

[0095] The cable samples prepared in the above Examples 1-3 and Comparative Examples 1-7 are subjected to performance detection according to the following method: Thermal conductivity of insulating layer: according to the standard ASTM E1461, the thermal conductivity of the insulating layer material at 100°C is tested by laser flash method.

[0096] Fire integrity: according to the standard GB / T 19216.21-2003, the cable sample is burned in a flame at 950±40°C while applying rated voltage, and the longest time for maintaining circuit integrity without breakdown is recorded.

[0097] Tensile strength of outer sheath: according to the standard GB / T 528, the tensile strength of the outer sheath is tested.

[0098] Wear resistance of outer sheath: using a Taber wear tester, the mass loss after 1000 revolutions of wear is tested under the condition of 1kg load and CS-17 grinding wheel.

[0099] Overall density of cable: the overall density of the finished cable product is measured by Archimedes drainage method.

[0100] Filling interface bonding evaluation: the cable core is cut along the radial direction, the interface between the filling layer 4 and the insulation layer 2 is observed under a scanning electron microscope, and the bonding tightness is evaluated.

[0101] Table 1: comprehensive performance test results of examples and comparative examples According to Table 1, it can be seen that: Examples 1, 2 and 3 all show excellent comprehensive performance. With the change of the content of each component and the process parameters in the set range from the lowest value of example 1 to the highest value of example 3, the thermal conductivity, fire resistance, mechanical strength and wear resistance of the cable show a steady upward trend. This proves that the parameter range defined in the application is an effective range, and the performance can be optimized by adjusting the parameters. Compared with comparative example 1, the product of the application has obvious improvement in each key indicator, which proves the significant progress of the overall technical scheme of the application. Comparative example 2 lacks silica sol and comparative example 7 uses epoxy resin, which cannot form an interpenetrating network structure; the single-stage baking in comparative example 6 destroys the network formation conditions, and the tensile strength and wear resistance of the outer sheath show a cliff-like drop, which is much worse than example 2, proving that the composite coating liquid composed of organosilicon modified polyimide and inorganic silica sol, and the programmed curing process through stepwise temperature rise, is an indispensable core technical means to build a high-strength and high-wear-resistant outer sheath. Comparative example 5 uses ordinary high-silica glass fiber, and its tensile strength 9.5 MPa and fire resistance time 110 min are significantly lower than example 2 using basalt fiber, 15.5 MPa, 145 min, which shows that the selection of continuous basalt fiber as the reinforcing skeleton is crucial to improve the mechanical properties and overall high-temperature resistance of the outer sheath. The insulation layer of comparative example 3 lacks flaky hexagonal boron nitride, and its thermal conductivity coefficient decreases significantly; at the same time, the filling layer uses conventional fillers, which leads to a significant increase in the overall density of the cable and loses the lightweight advantage, which shows that flaky hexagonal boron nitride plays a key role in improving the heat dissipation efficiency of the insulation layer, and composite lightweight fillers play a key role in achieving cable lightweight. Comparative example 4 does not modify the filling material with silane coupling agent, and although there is no sharp change in each macroscopic performance indicator, it shows a gap and poor bonding in the microscopic interface evaluation, which shows that the unmodified filler has poor compatibility with the matrix, which can easily lead to interface separation during long-term use, affecting the thermal insulation stability and long-term reliability, therefore, the surface chemical modification of lightweight thermal insulation fillers is an important guarantee for the structural integrity and performance stability of the filling layer.

Claims

1. A shielded, high temperature resistant, compensated cable comprising an alloy wire (1), characterized in that, The alloy wire (1) is two groups, the alloy wire (1) is provided with multiple groups in a rectangular array distribution four groups, the outer wall of multiple alloy wires (1) is fixedly connected with an insulating layer (2), the outer wall of the insulating layer (2) is fixedly connected with a shielding layer (3), the outer wall of the shielding layer (3) is fixedly connected with a filling layer (4), the outer wall of the filling layer (4) is fixedly connected with an outer sheath (5), the insulating layer (2) and the shielding layer (3) are fixedly connected with a first layer of wrapping tape (6), the shielding layer (3) and the filling layer (4) are provided with a second layer of wrapping tape (6), the filling layer (4) and the outer sheath (5) are provided with a third layer of wrapping tape (6), and the outer sheath (5) is provided with two layers and is provided with a fourth layer of wrapping tape (6) in the middle.

2. The preparation method of the shielded special high temperature resistant compensation cable, applied to the shielded special high temperature resistant compensation cable according to claim 1, characterized in that, It comprises the following steps: S1, the composite ceramic insulation material is coated on the alloy wire (1) conductor, and crosslinking vulcanization is carried out, forming an insulating layer (2), and then a first layer of wrapping tape (6) is wrapped outside the insulating layer (2), obtaining an insulating wire core; S2, multiple insulating wire cores are stranded into cables, and light thermal insulation composite filling material is filled into the gap between the insulating wire cores during the stranding process and is solidified, forming a filling layer (4), obtaining a cable core; S3, a second layer of wrapping tape (6) is wrapped outside the cable core in turn, a metal shielding layer (3) is formed by weaving, and a third layer of wrapping tape (6) is wrapped outside the metal shielding layer (3); S4, reinforcing fiber skeleton is woven outside the third layer of wrapping tape (6), and the reinforcing fiber skeleton is impregnated and coated and programmed heat curing treatment, forming an outer sheath (5).

3. The preparation method of the shielded high temperature resistant compensation cable according to claim 2, characterized in that, In the step S1, the composite ceramic insulation material comprises 100 parts of methyl vinyl silicone rubber, 40-60 parts of ceramic filler, 15-25 parts of fumed white carbon black, 5-15 parts of zinc borate, and 5-10 parts of flaky hexagonal boron nitride, by mass fraction.

4. The preparation method of the shielded high temperature resistant compensation cable according to claim 2, characterized in that, In the step S2, the following pretreatment step is further included before filling: the surface of the silica aerogel and hollow glass microspheres as light thermal insulation fillers is chemically modified by using a silane coupling agent.

5. The preparation method of the shielded high temperature resistant compensation cable according to claim 2 or 4, characterized in that, In the step S2, the light thermal insulation composite filling material is made of raw materials including two-component addition type liquid silicone rubber, surface-chemically modified silica aerogel and hollow glass microspheres, and aluminum hydroxide flame retardant.

6. The preparation method of the shielded high temperature resistant compensation cable according to claim 2, characterized in that, In the step S4, the reinforcing fiber skeleton is a continuous basalt fiber woven layer.

7. The preparation method of the shielded high temperature resistant compensation cable according to claim 2 or 6, characterized in that, In the step S4, the impregnated coating material is an organic and inorganic nano composite coating liquid, which is made of raw materials including organosilicon modified polyimide emulsion, inorganic binder silica sol, and nano silicon carbide wear-resistant filler.

8. The preparation method of the shielded high temperature resistant compensation cable according to claim 6, characterized in that, In the step S4, the programmed heat curing treatment comprises the following steps: The impregnated cable semi-finished product is sent into a heating temperature zone, which comprises three regions; The temperature of the first region is 80-100℃, the temperature of the second region is 150-200℃, and the temperature of the third region is 250-300℃, which is stepped up by an oven, so as to build an organic and inorganic interpenetrating network structure in the outer sheath (5).

9. The method for preparing a shielded high-temperature resistant compensating cable according to claim 2, characterized in that, In step S2, the insulated wire core is stranded at a pitch of 80-120 mm, and the filled cable core is cured on line by an infrared heating channel at 130-150°C.

10. The method for preparing a shielded high-temperature resistant compensating cable according to claim 2, characterized in that, In step S3, the metal shielding layer (3) is woven by tin-plated copper wire with a diameter of 0.10-0.15 mm, and the coverage is ≥85%. After the preparation, the following steps are performed: wrapping a fourth layer of wrapping tape (6) outside the outer sheath (5), and repeating step S4 completely to prepare a second layer of outer sheath.